Q must be positive in F.
F. r squared will be positive, because any number times itself is positive, and to get a positive number for the answer, the two numbers you multiply need to be the same sign. If r squared is positive, q must be too.
G. q does not have to be positive. If r is a negative number, then q can be negative. Say q=-2 and r=-3. -2-(-3) changes to -2+3, which equals 1.
H. Again, q can be negative if r is negative (two negative numbers multiplied together equals a positive answer.
J. q can be negative because even a negative number turns positive when squared.
Hope this helped you. :)
Answer:
4 1/3
Step-by-step explanation:
:) Can i get Brainliest? :)
Answer:
You can choose which equation below suits your taste but I recommend the 2n + 1 = -33.
Step-by-step explanation:
![(n) + (n + 1) = - 33 \\ 2n + 1 = - 33 \\ 2n = - 32 \\ n = - 16](https://tex.z-dn.net/?f=%28n%29%20%2B%20%28n%20%2B%201%29%20%3D%20%20-%2033%20%5C%5C%202n%20%2B%201%20%3D%20%20-%2033%20%5C%5C%202n%20%3D%20%20-%2032%20%5C%5C%20n%20%3D%20%20-%2016)
$5.49 + $10.49=$15:49 there’s your answer
Answer:
<h2>X=6</h2>
Step-by-step explanation:
<h3>to understand this</h3><h3>you need to know about:</h3>
<h3>let's solve:</h3>
![\sf cancel \: 4 \: from \: both \: sides : \\ \sf \implies \: 3x + 4 - 4 = 22 - 4 \\ \implies \sf \: 3x = 18](https://tex.z-dn.net/?f=%20%5Csf%20cancel%20%5C%3A%204%20%5C%3A%20from%20%5C%3A%20both%20%5C%3A%20sides%20%3A%20%20%5C%5C%20%20%5Csf%20%20%20%5Cimplies%20%5C%3A%203x%20%2B%204%20-%204%20%3D%2022%20-%204%20%5C%5C%20%20%5Cimplies%20%5Csf%20%5C%3A%203x%20%3D%2018)
![\sf divide \: both \: sides \: by \: 3 : \\ \sf \bcancel \frac{3x}{3} = \frac{ \cancel{18} \: \: ^{6} }{ \cancel{ \: 3}} \\ \therefore \rm \: x = 6](https://tex.z-dn.net/?f=%20%5Csf%20divide%20%5C%3A%20both%20%5C%3A%20sides%20%5C%3A%20by%20%5C%3A%203%20%3A%20%20%5C%5C%20%20%5Csf%20%20%5Cbcancel%20%5Cfrac%7B3x%7D%7B3%7D%20%20%3D%20%20%5Cfrac%7B%20%20%5Ccancel%7B18%7D%20%5C%3A%20%20%5C%3A%20%20%5E%7B6%7D%20%7D%7B%20%5Ccancel%7B%20%5C%3A%203%7D%7D%20%20%5C%5C%20%20%5Ctherefore%20%5Crm%20%5C%3A%20x%20%3D%206)